RISET PERILAKU KONSUMEN PADA MAHASISWA AKTIF PROGRAM STUDI ILMU KOMUNIKASI UNIVERSITAS BUNDA MULIA TAHUN AJARAN 2011 – 2012 SEBAGAI PENGUNJUNG LAWSON’S STATION-LODAN - Rustono Farady Marta (SEMIOTIKA: Jurnal Komunikasi, 2014)
Business prospects for a concept of convenience stores are becoming increasingly brighter for business today. One brand of convenience stores emerging in Indonesia is Lawson's Station. The concept of practical and convenient place served to segment the youth market, in accordance with that carried the tagline "Your One Stop for Quality Time". Lawson's Station, which opened branches in the University of Bunda Mulia (UBM) in Jakarta at the end of 2011, then got a good response from the entire academic community UBM. It is evident from the many customers who come to visit every day. Therefore, the researchers wanted to know the consumer behavior is analyzed from three components (tri-component attitude model) include: cognitive, affective, and conative. This study uses quantitative methods, where the collection of primary data obtained through the questionnaire using a nominal scale data, and then supported by secondary data from observation, documentation, and supporting literature. Data analysis techniques that have been tested for validity and reliability of the research instrument deserves to be used, then engage students UBM communication science courses as a subject of study in itself.Keywords : Consumer Behaviour, Three Component Attitude Models, Lawson’s Station